Theoretical description of the ligand function for ionoselective electrodes reversible to metal anion complexes. 3. Modeling of the electrode response in ligand and foreign ions solutions using the multi-species approach model - Egorov, Vladimir V.; Siamionau, Andrei V.; Novakovskii, Andrei D.; Akayeu, Yauhen B. (Journal of the Belarusian State University. Chemistry, 2021)
A description for the ligand function of the tetrathiocyanatozincate selective electrode, has been proposed, using a multi-species approach model. This model takes into account simultaneous phase-boundary, diffusion-controlled, processes of ion exchange between tetrathiocyanatozincate, thyocyanate and foreign ions unable to form zinc complexes, as well as distribution of the neutral zinc complex between phases, partial decomposition of quaternary ammonium tetrathiocyanatozincate salt and stepwise complex formation processes in water phase. The model is based on solving the system of equations describing several interphase and intraphase equilibria, assuming that diffusion flows of all membrane and solution components at the phase boundary are stationary. It provides the adequate description of tetrathiocyanatozincate selective electrode in solutions of the ligand, foreign ions and mixed solutions of the above, and predicts the effect of zinc chloride concentration in the sample solution upon electrode function slopes, lower detection limits and selectivity coefficients.